A Comparative Perspective between Romania and the Russian Federation regarding Life Insurance - Loredana Nicoletta MEGA; Maria Loredana POPESCU (Revista de Management Comparat International)
Life insurance plays a crucial role in financial planning, risk management, and economic stability. Life insurance is a critical financial instrument that provides economic security to individuals and their families by mitigating the financial impact of unforeseen death. It serves as a risk management tool, enabling wealth transfer, estate planning, and long-term financial stability. This paper reviews the historical development of life insurance, factors influencing consumer demand, market trends, and economic significance. Additionally, it explores challenges faced by the industry, including regulatory constraints, demographic shifts, and technological advancements. The future of life insurance is likely to be shaped by digital transformation, data analytics, and personalized policy offerings. Understanding life insurance’s role in financial planning is essential for both consumers and policymakers in ensuring economic resilience and security.